Lithography beyond light: Microcontact printing with monolayer resists - Biebuyck, H. A.; Larsen, N. B.; Delamarche, E.; Michel, B. (IBM journal of research and development, 1997)
A high-resolution lithography based on the transfer of pattern from an elastomeric `stamp' to a solid substrate through conformal contact is presented. The stamp which was formed by curing poly(dimethyl siloxane) on a master with the negative of the desired surface provides an `ink' that forms a self-assembled monolayer (SAM) on a solid surface through covalent, chemical reaction. The contacts results in the interaction between substrate and stamp that allow the transport of material from stamp to substrate. Microcontact printing with SAMs forms part of a convenient lithographic system not subject to diffraction or depth of focus limitations while still providing simultaneous transfer of patterned features.